Integrated Governance approaches to flood disaster management in Malaysia using risk reduction tools leading to sustainable development. - Hassan, Mohd Sayuti

(untitled)
The sustainable effectiveness of national Disaster Risk Reduction (DRR) strategy depends on well-coordinate governance mechanisms across sectors and at all levels.